PENINGKATAN KINERJA KEPALA SEKOLAH DALAM MELAKSANAKAN SUPERVISI AKADEMIK MELALUI BIMBINGAN TERPROGRAM DI SEKOLAH DASAR GUGUS DWIJA BHAKTI KECAMATAN TEMBARAK TAHUN 2013 - Suharyanto . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
This research is motivated that the performance of the principal in academic supervision in elementary schools is still weak. To overcome this is done mentoring programs. Issues examined how to increase the performance of the principal on the competence of academic supervision after guidance programmed by researches, and the objectives of penelitian school action are (1) to increase the performance of principal in carrying out academic supervision after guidance programmed by researches, (2) describe the change in the behavior of the principal after getting guidance from researches programmed. This study is an action research school with two cycles, each cycle consisting of four phases, namely : planning, pelaksanaan, observation and reflection. Constituting the subject of this study all the heads of primary school in the District Cluster Dwija Bhakti Tembarak 2013. Data were analyzed qualitatively and quantitatively by comparing the results of pre-cycle, the first cycle and the second cycle with indicators of success of at least 75% or 6 school entrance on both criteria or obtaining a value betweem 70 to 85. The results showed that : (1) an increase in the average value of the whole dimension of the performance of principals in implementing the academic supervision of pre-cycle into 19.92 to 6.76 in the first cycle and increased significantly in the second cycle into 70.55, results this has reached the target, and (2) the behavior of school principals become more open to accept input in carrying out academic supervision, with a value of 67 in the first cycle increased to 77 in the second cycle. It can be concluded that through programmatic guidance can improve the performance of school principals in implementing academic supervision in elementary schools Dwija Bhakti force District of Tembarak in 2013. Keywords : Guidance programmed, performance, academic supervision.